Preparation method of lithium battery containing polymer solid electrolyte

By mixing with lithium salt, leading agent, and plasticizer in situ for in situ aggregation in lithium batteries to form a polymer -containing solid electrolyte, solving the problem of low existing polymer electrolyte conductivity and narrow stable windows It realizes lithium batteries with high energy density and security.

CN119340494APending Publication Date: 2025-01-21FPR CONNECTIVITY TECH INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411402402.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing polymer electrolytes have low conductivity and narrow electrochemical stability windows at room temperature, which affects the performance of lithium batteries.

Method used

Heterocyclic monomers are mixed with lithium salts, initiators and plasticizers, and then polymerized in situ by standing at high temperatures to form a polymer-containing solid electrolyte.

Benefits of technology

Improved electrochemical properties, matching high -voltage positive materials to obtain high -energy density lithium batteries, enhancing the safety and cycle performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340494A_ABST
    Figure CN119340494A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a lithium battery containing a polymer solid electrolyte, which comprises the following steps: S1, preparing a solution with a preset concentration by taking a lithium salt as a solute and a plasticizer as a solvent; and S2, uniformly mixing a monomer and the solution obtained in the step S1 to obtain a mixed solution, then adding an initiator, and uniformly mixing to obtain a precursor. And S3, assembling the lithium battery by using the negative electrode of the lithium battery, the positive electrode of the lithium battery and the diaphragm. And S4, injecting the precursor obtained in the step S2 into the lithium battery, and carrying out high-temperature standing operation on the precursor in a temperature range of 40-100 DEG C for 1-12 hours to obtain the lithium battery containing the polymer solid electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a method for preparing a lithium battery containing a polymer solid electrolyte. Background Art

[0002] With the in-depth marketization of electric vehicles and energy storage facilities, the safety of lithium-ion batteries also needs to be further improved. Because of the higher safety of solid-state electrolytes, the introduction of safer lithium batteries is of far-reaching significance. Therefore, most lithium batteries use solid electrolytes inside. Polymer solid electrolytes have good flexibility and excellent processing performance, which is conducive to reducing the interface impedance between electrodes and is easier to industrialize. Therefore, polymer solid electrolytes are often used in the preparation process of lithium batteries. However, polymer solid electrolytes have the disadvantages of low conductivity and narrow electrochemical stability window at room temperature, which will affect battery performance. Therefore, there is a technical problem that existing polymer electrolytes will have an adverse effect on battery performance.

[0003] Therefore, it is necessary to provide a method for preparing a lithium battery containing a polymer solid electrolyte to solve the above technical problems. Summary of the invention

[0004] The present invention provides a method for preparing a lithium battery containing a polymer solid electrolyte, which effectively solves the technical problem that the existing polymer electrolyte may have adverse effects on battery performance.

[0005] The present invention provides a method for preparing a lithium battery containing a polymer solid electrolyte, which comprises the following steps:

[0006] S1: using lithium salt as solute and plasticizer as solvent to prepare a solution of preset concentration, wherein the preset concentration is 0.8 mol / L-2 mol / L concentration of the lithium salt in the plasticizer;

[0007] S2: uniformly mixing the monomer and the solution obtained in step S1 to obtain a mixed solution, and then adding an initiator and mixing them uniformly to obtain a precursor; wherein the mass fraction of the monomer in the mixed solution is 20-80%; the mass of the initiator is 0-20% of the mass of the monomer;

[0008] S3: Assembling a lithium battery with a negative electrode of a lithium battery, a positive electrode of a lithium battery and a separator;

[0009] S4: injecting the precursor obtained in step S2 into the lithium battery, and subjecting the precursor to a high-temperature standing operation within a temperature range of 40-100°C, and obtaining a lithium battery containing a polymer solid electrolyte after high-temperature standing for 1-12 hours, wherein the injection amount of the precursor is determined by the unit area of ​​the diaphragm, and the injection amount of the precursor is 20-150 μL.

[0010] In the method for preparing a lithium battery containing a polymer solid electrolyte of the present invention, it is characterized in that, in the step S2, the mass of the initiator is 5-10% of the mass of the monomer.

[0011] In the method for preparing a lithium battery containing a polymer solid electrolyte of the present invention, in step S4, the temperature of the high temperature static state is 70-80° C.,

[0012] In the method for preparing a lithium battery containing a polymer solid electrolyte of the present invention, in step S4, the high temperature standing time is 2-4 hours.

[0013] In the preparation method of a lithium battery containing a polymer solid electrolyte described in the present invention, the monomer is a cyclic ether, a cyclic lactone or a cyclic carbonate, and the cyclic ether is composed of a mixture of one or more of 1,3,5-trioxane, 1,3-dioxolane, ethylene oxide, epichlorohydrin, 1,2-propylene oxide, 1,3-propylene oxide, 1,2-butylene oxide, and tetrahydrofuran; the cyclic lactone is composed of a mixture of one or more of ε-caprolactone, γ-butyrolactone, δ-valerolactone, and lactide; and the cyclic carbonate is composed of a mixture of one or more of vinyl ethylene carbonate and trimethylene carbonate.

[0014] In the preparation method of the lithium battery containing polymer solid electrolyte described in the present invention, the initiator is composed of one or more mixtures of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorooxalatoborate, stannous isooctanoate, aluminum trifluoromethylsulfonate, boron trifluoride ethyl ether, and tris(pentafluorophenyl)borane.

[0015] In the preparation method of the lithium battery containing polymer solid electrolyte described in the present invention, the lithium salt is composed of any one or more mixtures of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium difluorooxalatoborate, lithium perchlorate, lithium bisoxalatoborate, lithium trichloromethylsulfonate, lithium bistrifluoromethylsulfonyl imide, and lithium bisfluorosulfonyl imide.

[0016] In the preparation method of the lithium battery containing polymer solid electrolyte described in the present invention, the plasticizer is composed of one or more mixtures of ethylene carbonate, propylene carbonate, vinylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, fluoroethylene carbonate, 2,2,2-trifluoro-N,N-dimethylacetamide, methyl trifluoroethyl carbonate, and triethyl phosphate.

[0017] In the preparation method of a lithium battery containing a polymer solid electrolyte described in the present invention, the negative electrode of the lithium battery is any one of graphite, soft carbon, hard carbon, silicon, and lithium metal; the positive electrode of the lithium battery is any one of lithium iron phosphate, nickel-cobalt-manganese ternary material, nickel-cobalt-aluminum ternary material, lithium cobaltate, and lithium manganate; and the diaphragm is any one of a polyethylene diaphragm, a polypropylene diaphragm, a polyimide diaphragm, a cellulose diaphragm, a glass fiber diaphragm, a polyethylene terephthalate diaphragm, and a non-woven fabric diaphragm.

[0018] A method for manufacturing a lithium battery, comprising:

[0019] Fluorinated ethylene carbonate and methyl trifluoroethyl carbonate are mixed in a mass ratio of 1:1 to obtain a plasticizer, and 5 ml of the plasticizer is taken; 0.374 g of lithium bis(fluorosulfonyl)imide and 0.037 g of lithium hexafluorophosphate are added to the 5 ml of the plasticizer, wherein the lithium bis(fluorosulfonyl)imide and the lithium hexafluorophosphate are lithium salts, and then 2.264 g of 1,3,5-trioxane is added, wherein the 1,3,5-trioxane is a monomer, and after uniform mixing, a first mixed solution is obtained, and then 0.226 g of lithium difluorooxalate borate is added, wherein the lithium difluorooxalate borate is an initiator; after stirring for 30 minutes, a precursor is obtained;

[0020] A soft-pack battery is assembled using graphite as the negative electrode of the lithium battery, a nickel-cobalt-manganese ternary material as the positive electrode of the lithium battery, and polypropylene as a separator; 2 mL of the precursor is injected into the battery, and after standing at room temperature for 24 hours, it is stood at a high temperature of 80°C for 2 hours to obtain a lithium battery containing a polymer solid electrolyte.

[0021] Compared with the prior art, the present invention has the following beneficial effects: the present invention provides a method for preparing a lithium battery containing a polymer solid electrolyte, wherein the polymer solid electrolyte uses a heterocyclic ring as a monomer, is mixed with an initiator, a lithium salt and a plasticizer, and then is injected into a diaphragm, and the heterocyclic ring monomer undergoes in-situ polymerization inside the battery according to a ring-opening polymerization mechanism. Therefore, the polymer solid electrolyte has excellent electrochemical properties, and a lithium battery with a high energy density can be obtained by matching a high-voltage positive electrode material. Therefore, the lithium battery containing a polymer solid electrolyte has good battery performance. The polymer solid electrolyte uses a lithium salt as an initiator, which is conducive to maintaining the purity of the electrolyte system and can improve the performance of the battery. The electrolyte is solid, which effectively improves the safety of the battery. The electrolyte is finally solidified between the electrodes, which significantly improves the interface contact between the electrodes and improves the cycle performance of the battery. Therefore, the lithium battery containing a polymer solid electrolyte not only has high safety, but also has good battery performance. The technical problem that the existing polymer electrolyte has an adverse effect on battery performance is effectively solved. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments. The drawings described below are only drawings corresponding to some embodiments of the present invention.

[0023] Figure 1 The present invention is a process flow chart of the preparation method of a lithium battery containing a polymer solid electrolyte. DETAILED DESCRIPTION

[0024] The technical solution of the invention will be described in detail below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the invention and are not used to limit the scope of the invention. After reading the invention, various equivalent forms of modifications to the invention made by those skilled in the art all fall within the scope defined by the claims attached to this application.

[0025] The terms "first", "second", etc. in the present invention are used for descriptive purposes only and should not be understood as indicating or implying relative importance, and should not be used as a limitation on the order of precedence.

[0026] The present invention provides a method for preparing a lithium battery containing a polymer solid electrolyte, which comprises the following steps:

[0027] S1: using lithium salt as solute and plasticizer as solvent to prepare a solution of preset concentration, wherein the preset concentration is 0.8 mol / L-2 mol / L concentration of the lithium salt in the plasticizer;

[0028] S2: uniformly mixing the monomer and the solution obtained in step S1 to obtain a mixed solution, and then adding an initiator and mixing them uniformly to obtain a precursor; wherein the mass fraction of the monomer in the mixed solution is 20-80%; the mass of the initiator is 0-20% of the mass of the monomer;

[0029] S3: Assembling a lithium battery with a negative electrode of a lithium battery, a positive electrode of a lithium battery and a separator;

[0030] S4: injecting the precursor obtained in step S2 into the lithium battery, and subjecting the precursor to a high-temperature standing operation within a temperature range of 40-100°C, and obtaining a lithium battery containing a polymer solid electrolyte after high-temperature standing for 1-12 hours, wherein the injection amount of the precursor is determined by the unit area of ​​the diaphragm, and the injection amount of the precursor is 20-150 μL.

[0031] In step S2 of the present invention, the mass of the initiator is 5-10% of the mass of the monomer.

[0032] In step S4 of the present invention, the high temperature static temperature is 70-80°C.

[0033] In step S4 of the present invention, the high temperature standing time is 2-4 hours.

[0034] In the present invention, the monomer is a cyclic ether, a cyclic lactone or a cyclic carbonate. The cyclic ether is composed of a mixture of one or more of 1,3,5-trioxane, 1,3-dioxolane, ethylene oxide, epichlorohydrin, 1,2-propylene oxide, 1,3-propylene oxide, 1,2-butylene oxide and tetrahydrofuran; the cyclic lactone is composed of a mixture of one or more of ε-caprolactone, γ-butyrolactone, δ-valerolactone and lactide; the cyclic carbonate is composed of a mixture of one or more of vinyl ethylene carbonate and trimethylene carbonate.

[0035] In the present invention, the initiator is composed of a mixture of one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorooxalatoborate, stannous isooctanoate, aluminum trifluoromethanesulfonate, boron trifluoride ethyl ether, and tris(pentafluorophenyl)borane.

[0036] In the present invention, the lithium salt is composed of any one or more mixtures of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium difluorooxalatoborate, lithium perchlorate, lithium bisoxalatoborate, lithium trichloromethylsulfonate, lithium bistrifluoromethylsulfonyl imide, and lithium bisfluorosulfonyl imide.

[0037] In the present invention, the plasticizer is composed of one or more mixtures of ethylene carbonate, propylene carbonate, vinylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, fluoroethylene carbonate, 2,2,2-trifluoro-N,N-dimethylacetamide, methyl trifluoroethyl carbonate, and triethyl phosphate.

[0038] In the present invention, the negative electrode of the lithium battery is any one of graphite, soft carbon, hard carbon, silicon, and lithium metal; the positive electrode of the lithium battery is any one of lithium iron phosphate, nickel-cobalt-manganese ternary material, nickel-cobalt-aluminum ternary material, lithium cobalt oxide, and lithium manganese oxide; the diaphragm is any one of a polyethylene diaphragm, a polypropylene diaphragm, a polyimide diaphragm, a cellulose diaphragm, a glass fiber diaphragm, a polyethylene terephthalate diaphragm, and a non-woven fabric diaphragm.

[0039] The present invention also provides a method for preparing a lithium battery. Example 1 of the method for preparing a lithium battery is as follows:

[0040] Fluorinated ethylene carbonate and methyl trifluoroethyl carbonate are mixed in a mass ratio of 1:1 to obtain a plasticizer, and 5 ml of the plasticizer is taken; 0.374 g of lithium bis(fluorosulfonyl)imide and 0.037 g of lithium hexafluorophosphate are added to the 5 ml of the plasticizer, wherein the lithium bis(fluorosulfonyl)imide and the lithium hexafluorophosphate are lithium salts, and then 2.264 g of 1,3,5-trioxane is added, wherein the 1,3,5-trioxane is a monomer, and after uniform mixing, a first mixed solution is obtained, and then 0.226 g of lithium difluorooxalate borate is added, wherein the lithium difluorooxalate borate is an initiator; wherein the mass of the initiator is 10% of the mass of the monomer; after stirring for 30 minutes, a precursor is obtained;

[0041] A soft-pack battery is assembled using graphite as the negative electrode of the lithium battery, a nickel-cobalt-manganese ternary material as the positive electrode of the lithium battery, and polypropylene as a separator; 2 mL of the precursor is injected into the battery, and after standing at room temperature for 24 hours, it is stood at a high temperature of 80°C for 2 hours to obtain a lithium battery containing a polymer solid electrolyte.

[0042] Example 2 of the preparation method of the lithium battery is as follows:

[0043] Fluorinated ethylene carbonate and methyl trifluoroethyl carbonate are mixed in a mass ratio of 1:1 to obtain a plasticizer, and 5 ml of the plasticizer is taken; 0.374 g of lithium bis(fluorosulfonyl)imide and 0.037 g of lithium hexafluorophosphate are added to the 5 ml of the plasticizer, wherein the lithium bis(fluorosulfonyl)imide and the lithium hexafluorophosphate are lithium salts, and then 2.264 g of 1,3,5-trioxane is added, wherein the 1,3,5-trioxane is a monomer, and after uniform mixing, a first mixed solution is obtained, and then 0.226 g of boron trifluoride ether is added, wherein the boron trifluoride ether is an initiator; wherein the mass of the initiator is 10% of the mass of the monomer; after stirring for 30 minutes, a precursor is obtained;

[0044] A soft-pack battery is assembled using graphite as the negative electrode of the lithium battery, a nickel-cobalt-manganese ternary material as the positive electrode of the lithium battery, and polypropylene as a separator; 2 mL of the precursor is injected into the battery, and after standing at room temperature for 24 hours, it is stood at a high temperature of 80°C for 2 hours to obtain a lithium battery containing a polymer solid electrolyte.

[0045] Example 3 of the preparation method of the lithium battery is as follows:

[0046] Fluorinated ethylene carbonate and methyl trifluoroethyl carbonate are mixed in a mass ratio of 1:1 to obtain a plasticizer, and 5 ml of the plasticizer is taken; 0.374 g of lithium bis(fluorosulfonyl)imide and 0.037 g of lithium hexafluorophosphate are added to the 5 ml of the plasticizer, wherein the lithium bis(fluorosulfonyl)imide and the lithium hexafluorophosphate are lithium salts, and then 2.264 g of 1,3,5-trioxane is added, wherein the 1,3,5-trioxane is a monomer, and after uniform mixing, a first mixed solution is obtained, and then 0.226 g of aluminum trifluoromethylsulfonate is added, wherein the aluminum trifluoromethylsulfonate is an initiator; wherein the mass of the initiator is 10% of the mass of the monomer; after stirring for 30 minutes, a precursor is obtained;

[0047] A soft-pack battery is assembled using graphite as the negative electrode of the lithium battery, a nickel-cobalt-manganese ternary material as the positive electrode of the lithium battery, and polypropylene as a separator; 2 mL of the precursor is injected into the battery, and after standing at room temperature for 24 hours, it is stood at a high temperature of 80°C for 2 hours to obtain a lithium battery containing a polymer solid electrolyte.

[0048] Example 4 of the preparation method of the lithium battery is as follows:

[0049] Fluorinated ethylene carbonate and methyl trifluoroethyl carbonate are mixed in a mass ratio of 1:1 to obtain a plasticizer, and 5 ml of the plasticizer is taken; 0.374 g of lithium bis(fluorosulfonyl)imide and 0.037 g of lithium hexafluorophosphate are added to the 5 ml of the plasticizer, wherein the lithium bis(fluorosulfonyl)imide and the lithium hexafluorophosphate are lithium salts, and then 2.264 g of 1,3,5-trioxane is added, wherein the 1,3,5-trioxane is a monomer, and after uniform mixing, a first mixed solution is obtained, and then 0.226 g of stannous isooctanoate is added, wherein the stannous isooctanoate is an initiator; wherein the mass of the initiator is 10% of the mass of the monomer; after stirring for 30 minutes, a precursor is obtained;

[0050] A soft-pack battery is assembled using graphite as the negative electrode of the lithium battery, a nickel-cobalt-manganese ternary material as the positive electrode of the lithium battery, and polypropylene as a separator; 2 mL of the precursor is injected into the battery, and after standing at room temperature for 24 hours, it is stood at a high temperature of 80°C for 2 hours to obtain a lithium battery containing a polymer solid electrolyte.

[0051] Example 5 of the preparation method of the lithium battery is as follows:

[0052] Fluorinated ethylene carbonate and methyl trifluoroethyl carbonate are mixed in a mass ratio of 1:1 to obtain a plasticizer, and 5 ml of the plasticizer is taken; 0.374 g of lithium bis(fluorosulfonyl)imide and 0.037 g of lithium hexafluorophosphate are added to the 5 ml of the plasticizer, wherein the lithium bis(fluorosulfonyl)imide and the lithium hexafluorophosphate are lithium salts, and then 2.264 g of 1,3,5-trioxane is added, wherein the 1,3,5-trioxane is a monomer, and after uniform mixing, a first mixed solution is obtained, and then 0.226 g of tri(pentafluorophenyl)borane is added, wherein the tri(pentafluorophenyl)borane is an initiator; wherein the mass of the initiator is 10% of the mass of the monomer; after stirring for 30 minutes, a precursor is obtained;

[0053] A soft-pack battery is assembled using graphite as the negative electrode of the lithium battery, a nickel-cobalt-manganese ternary material as the positive electrode of the lithium battery, and polypropylene as a separator; 2 mL of the precursor is injected into the battery, and after standing at room temperature for 24 hours, it is stood at a high temperature of 80°C for 2 hours to obtain a lithium battery containing a polymer solid electrolyte.

[0054] Example 6 of the preparation method of the lithium battery is as follows:

[0055] Fluorinated ethylene carbonate and methyl trifluoroethyl carbonate are mixed in a mass ratio of 1:1 to obtain a plasticizer, and 5 ml of the plasticizer is taken; 0.374 g of lithium bis(fluorosulfonyl)imide and 0.037 g of lithium hexafluorophosphate are added to the 5 ml of the plasticizer, wherein the lithium bis(fluorosulfonyl)imide and the lithium hexafluorophosphate are lithium salts, and then 2.264 g of 1,3,5-trioxane is added, wherein the 1,3,5-trioxane is a monomer, and after uniform mixing, a first mixed solution is obtained, and then 0.226 g of lithium hexafluorophosphate is added, wherein the lithium hexafluorophosphate is an initiator; wherein the mass of the initiator is 10% of the mass of the monomer; after stirring for 30 minutes, a precursor is obtained;

[0056] A soft-pack battery is assembled using graphite as the negative electrode of the lithium battery, a nickel-cobalt-manganese ternary material as the positive electrode of the lithium battery, and polypropylene as a separator; 2 mL of the precursor is injected into the battery, and after standing at room temperature for 24 hours, it is stood at a high temperature of 80°C for 2 hours to obtain a lithium battery containing a polymer solid electrolyte.

[0057] In Examples 2-6, the reaction process is the same as in Example 1, except that the type of initiator is changed, as shown in Table 1.

[0058] Table 1

[0059] Initiator <![CDATA[Conductivity (mS cm -1 )]]> Lithium ion migration number Example 1 Lithium difluorooxalate borate 2.39 0.78 Example 2 Boron trifluoride etherate 1.62 0.81 Example 3 Aluminum trifluoromethanesulfonate 1.83 0.79 Example 4 Stannous 2-octanoate 1.95 0.78 Example 5 Tris(pentafluorophenyl)borane 2.53 0.57 Example 6 Lithium hexafluorophosphate 2.71 0.53

[0060] The lithium ion migration number is one of the important parameters for evaluating battery performance. A higher lithium ion migration number can reduce the concentration polarization inside the battery and improve the electrochemical performance of the battery. Moreover, the higher the conductivity, the better the battery performance. The standard for high electrochemical performance of lithium batteries is set to a lithium ion migration number equal to 0.7. If the lithium ion migration number is greater than or equal to 0.7, it means that the lithium battery has high electrochemical performance. If the lithium ion migration number is greater than or equal to 0.7, it means that the lithium battery has high electrochemical performance. In Table 1, Example 1, Example 2, Example 3 and Example 4 meet the standard for high electrochemical performance of lithium batteries. Moreover, the conductivity of Example 1 is greater than the conductivity of Example 2, the conductivity of Example 1 is greater than the conductivity of Example 3, and the conductivity of Example 1 is greater than the conductivity of Example 4. The preparation method of Example 1 can make the battery performance better, and therefore, Example 1 is the best embodiment.

[0061] Example 7 of the preparation method of the lithium battery is as follows:

[0062] Fluorinated ethylene carbonate and methyl trifluoroethyl carbonate are mixed in a mass ratio of 1:1 to obtain a plasticizer, and 5 ml of the plasticizer is taken; 0.374 g of lithium bis(fluorosulfonyl)imide and 0.037 g of lithium hexafluorophosphate are added to the 5 ml of the plasticizer, wherein the lithium bis(fluorosulfonyl)imide and the lithium hexafluorophosphate are lithium salts, and then 2.264 g of 1,3,5-trioxane is added, wherein the 1,3,5-trioxane is a monomer, and after uniform mixing, a first mixed solution is obtained, and then 0 g of lithium difluorooxalate borate is added, wherein the lithium difluorooxalate borate is an initiator; wherein the mass of the initiator is 0% of the mass of the monomer; after stirring for 30 minutes, a precursor is obtained;

[0063] A soft-pack battery is assembled using graphite as the negative electrode of the lithium battery, a nickel-cobalt-manganese ternary material as the positive electrode of the lithium battery, and polypropylene as a separator; 2 mL of the precursor is injected into the battery, and after standing at room temperature for 24 hours, it is stood at a high temperature of 80°C for 2 hours to obtain a lithium battery containing a polymer solid electrolyte.

[0064] Example 8 of the preparation method of the lithium battery is as follows:

[0065] Fluorinated ethylene carbonate and methyl trifluoroethyl carbonate are mixed in a mass ratio of 1:1 to obtain a plasticizer, and 5 ml of the plasticizer is taken; 0.374 g of lithium bis(fluorosulfonyl)imide and 0.037 g of lithium hexafluorophosphate are added to the 5 ml of the plasticizer, wherein the lithium bis(fluorosulfonyl)imide and the lithium hexafluorophosphate are lithium salts, and then 2.264 g of 1,3,5-trioxane is added, wherein the 1,3,5-trioxane is a monomer, and after uniform mixing, a first mixed solution is obtained, and then 0.04528 g of lithium difluorooxalate borate is added, wherein the lithium difluorooxalate borate is an initiator; wherein the mass of the initiator is 2% of the mass of the monomer; after stirring for 30 minutes, a precursor is obtained;

[0066] A soft-pack battery is assembled using graphite as the negative electrode of the lithium battery, a nickel-cobalt-manganese ternary material as the positive electrode of the lithium battery, and polypropylene as a separator; 2 mL of the precursor is injected into the battery, and after standing at room temperature for 24 hours, it is stood at a high temperature of 80°C for 2 hours to obtain a lithium battery containing a polymer solid electrolyte.

[0067] Example 9 of the preparation method of the lithium battery is as follows:

[0068] Fluorinated ethylene carbonate and methyl trifluoroethyl carbonate are mixed in a mass ratio of 1:1 to obtain a plasticizer, and 5 ml of the plasticizer is taken; 0.374 g of lithium bis(fluorosulfonyl)imide and 0.037 g of lithium hexafluorophosphate are added to the 5 ml of the plasticizer, wherein the lithium bis(fluorosulfonyl)imide and the lithium hexafluorophosphate are lithium salts, and then 2.264 g of 1,3,5-trioxane is added, wherein the 1,3,5-trioxane is a monomer, and after uniform mixing, a first mixed solution is obtained, and then 0.1132 g of lithium difluorooxalate borate is added, wherein the lithium difluorooxalate borate is an initiator; wherein the mass of the initiator is 5% of the mass of the monomer; after stirring for 30 minutes, a precursor is obtained;

[0069] A soft-pack battery is assembled using graphite as the negative electrode of the lithium battery, a nickel-cobalt-manganese ternary material as the positive electrode of the lithium battery, and polypropylene as a separator; 2 mL of the precursor is injected into the battery, and after standing at room temperature for 24 hours, it is stood at a high temperature of 80°C for 2 hours to obtain a lithium battery containing a polymer solid electrolyte.

[0070] Embodiment 10 of the preparation method of the lithium battery is as follows,

[0071] Fluorinated ethylene carbonate and methyl trifluoroethyl carbonate are mixed in a mass ratio of 1:1 to obtain a plasticizer, and 5 ml of the plasticizer is taken; 0.374 g of lithium bis(fluorosulfonyl)imide and 0.037 g of lithium hexafluorophosphate are added to the 5 ml of the plasticizer, wherein the lithium bis(fluorosulfonyl)imide and the lithium hexafluorophosphate are lithium salts, and then 2.264 g of 1,3,5-trioxane is added, wherein the 1,3,5-trioxane is a monomer, and after uniform mixing, a first mixed solution is obtained, and then 0.3396 g of lithium difluorooxalate borate is added, wherein the lithium difluorooxalate borate is an initiator; wherein the mass of the initiator is 15% of the mass of the monomer; after stirring for 30 minutes, a precursor is obtained;

[0072] A soft-pack battery is assembled using graphite as the negative electrode of the lithium battery, a nickel-cobalt-manganese ternary material as the positive electrode of the lithium battery, and polypropylene as a separator; 2 mL of the precursor is injected into the battery, and after standing at room temperature for 24 hours, it is stood at a high temperature of 80°C for 2 hours to obtain a lithium battery containing a polymer solid electrolyte.

[0073] In Examples 7-10, the reaction process is the same as in Example 1, except that the mass fraction of the initiator to the monomer is changed, as shown in Table 2.

[0074] Table 2

[0075]

[0076]

[0077] The lithium ion migration number is one of the important parameters for evaluating battery performance. A higher lithium ion migration number can reduce the concentration polarization inside the battery and improve the electrochemical performance of the battery. Moreover, the higher the conductivity, the better the battery performance. The standard for high electrochemical performance of lithium batteries is set to a lithium ion migration number equal to 0.7. If the lithium ion migration number is greater than or equal to 0.7, it means that the lithium battery has high electrochemical performance. If the lithium ion migration number is greater than or equal to 0.7, it means that the lithium battery has high electrochemical performance. In Table 2, Example 1, Example 9 and Example 10 meet the standard for high electrochemical performance of lithium batteries. Moreover, the conductivity of Example 1 is greater than the conductivity of Example 9, and the conductivity of Example 1 is greater than the conductivity of Example 9. The preparation method of Example 1 can make the battery performance better, and therefore, Example 1 is the best embodiment.

[0078] The preparation method of the lithium battery in Example 11 is as follows:

[0079] Fluorinated ethylene carbonate and methyl trifluoroethyl carbonate are mixed in a mass ratio of 1:1 to obtain a plasticizer, and 5 ml of the plasticizer is taken; 0.374 g of lithium bis(fluorosulfonyl)imide and 0.037 g of lithium hexafluorophosphate are added to the 5 ml of the plasticizer, wherein the lithium bis(fluorosulfonyl)imide and the lithium hexafluorophosphate are lithium salts, and then 2.264 g of 1,3,5-trioxane is added, wherein the 1,3,5-trioxane is a monomer, and after uniform mixing, a first mixed solution is obtained, and then 0.226 g of lithium difluorooxalate borate is added, wherein the lithium difluorooxalate borate is an initiator; wherein the mass of the initiator is 10% of the mass of the monomer; after stirring for 30 minutes, a precursor is obtained;

[0080] A soft-pack battery is assembled using graphite as the negative electrode of the lithium battery, a nickel-cobalt-manganese ternary material as the positive electrode of the lithium battery, and polypropylene as a separator; 2 mL of the precursor is injected into the battery, and after standing at room temperature for 24 hours, it is stood at a high temperature of 80°C for 0.5 hours to obtain a lithium battery containing a polymer solid electrolyte.

[0081] Example 12 of the preparation method of the lithium battery is as follows,

[0082] Fluorinated ethylene carbonate and methyl trifluoroethyl carbonate are mixed in a mass ratio of 1:1 to obtain a plasticizer, and 5 ml of the plasticizer is taken; 0.374 g of lithium bis(fluorosulfonyl)imide and 0.037 g of lithium hexafluorophosphate are added to the 5 ml of the plasticizer, wherein the lithium bis(fluorosulfonyl)imide and the lithium hexafluorophosphate are lithium salts, and then 2.264 g of 1,3,5-trioxane is added, wherein the 1,3,5-trioxane is a monomer, and after uniform mixing, a first mixed solution is obtained, and then 0.226 g of lithium difluorooxalate borate is added, wherein the lithium difluorooxalate borate is an initiator; wherein the mass of the initiator is 10% of the mass of the monomer; after stirring for 30 minutes, a precursor is obtained;

[0083] A soft-pack battery is assembled using graphite as the negative electrode of the lithium battery, a nickel-cobalt-manganese ternary material as the positive electrode of the lithium battery, and polypropylene as a separator; 2 mL of the precursor is injected into the battery, and after standing at room temperature for 24 hours, it is stood at a high temperature of 80°C for 3 hours to obtain a lithium battery containing a polymer solid electrolyte.

[0084] Example 13 of the preparation method of the lithium battery is as follows,

[0085] Fluorinated ethylene carbonate and methyl trifluoroethyl carbonate are mixed in a mass ratio of 1:1 to obtain a plasticizer, and 5 ml of the plasticizer is taken; 0.374 g of lithium bis(fluorosulfonyl)imide and 0.037 g of lithium hexafluorophosphate are added to the 5 ml of the plasticizer, wherein the lithium bis(fluorosulfonyl)imide and the lithium hexafluorophosphate are lithium salts, and then 2.264 g of 1,3,5-trioxane is added, wherein the 1,3,5-trioxane is a monomer, and after uniform mixing, a first mixed solution is obtained, and then 0.226 g of lithium difluorooxalate borate is added, wherein the lithium difluorooxalate borate is an initiator; wherein the mass of the initiator is 10% of the mass of the monomer; after stirring for 30 minutes, a precursor is obtained;

[0086] A soft-pack battery is assembled using graphite as the negative electrode of the lithium battery, a nickel-cobalt-manganese ternary material as the positive electrode of the lithium battery, and polypropylene as a separator; 2 mL of the precursor is injected into the battery, and after standing at room temperature for 24 hours, it is stood at a high temperature of 80°C for 4 hours to obtain a lithium battery containing a polymer solid electrolyte.

[0087] Example 14 of the preparation method of the lithium battery is as follows,

[0088] Fluorinated ethylene carbonate and methyl trifluoroethyl carbonate are mixed in a mass ratio of 1:1 to obtain a plasticizer, and 5 ml of the plasticizer is taken; 0.374 g of lithium bis(fluorosulfonyl)imide and 0.037 g of lithium hexafluorophosphate are added to the 5 ml of the plasticizer, wherein the lithium bis(fluorosulfonyl)imide and the lithium hexafluorophosphate are lithium salts, and then 2.264 g of 1,3,5-trioxane is added, wherein the 1,3,5-trioxane is a monomer, and after uniform mixing, a first mixed solution is obtained, and then 0.226 g of lithium difluorooxalate borate is added, wherein the lithium difluorooxalate borate is an initiator; wherein the mass of the initiator is 10% of the mass of the monomer; after stirring for 30 minutes, a precursor is obtained;

[0089] A soft-pack battery is assembled using graphite as the negative electrode of the lithium battery, a nickel-cobalt-manganese ternary material as the positive electrode of the lithium battery, and polypropylene as a separator; 2 mL of the precursor is injected into the battery, and after standing at room temperature for 24 hours, it is stood at a high temperature of 80°C for 6 hours to obtain a lithium battery containing a polymer solid electrolyte.

[0090] In Examples 11-14, the reaction process is the same as in Example 1, except that the high temperature standing time is changed, as shown in Table 3.

[0091] Table 3

[0092] Standing time (h) <![CDATA[Conductivity (mS cm -1 )]]> Lithium ion migration number Example 1 2 2.39 0.78 Embodiment 11 0.5 3.37 0.28 Example 12 3 2.37 0.76 Example 13 4 2.29 0.75 Embodiment 14 6 2.27 0.73

[0093] The lithium ion migration number is one of the important parameters for evaluating battery performance. A higher lithium ion migration number can reduce the concentration polarization inside the battery and improve the electrochemical performance of the battery. Moreover, the higher the conductivity, the better the battery performance. The standard for high electrochemical performance of lithium batteries is set to a lithium ion migration number equal to 0.7. If the lithium ion migration number is greater than or equal to 0.7, it means that the lithium battery has high electrochemical performance. If the lithium ion migration number is greater than or equal to 0.7, it means that the lithium battery has high electrochemical performance. In Table 2, Example 1, Example 12, Example 13 and Example 14 meet the standard for high electrochemical performance of lithium batteries. Moreover, the conductivity of Example 1 is greater than the conductivity of Example 12. The conductivity of Example 1 is greater than the conductivity of Example 13, and the conductivity of Example 1 is greater than the conductivity of Example 14. The preparation method of Example 1 can make the battery performance better, and therefore, Example 1 is the best embodiment.

[0094] Example 15 of the preparation method of the lithium battery is as follows,

[0095] Fluorinated ethylene carbonate and methyl trifluoroethyl carbonate are mixed in a mass ratio of 1:1 to obtain a plasticizer, and 5 ml of the plasticizer is taken; 0.374 g of lithium bis(fluorosulfonyl)imide and 0.037 g of lithium hexafluorophosphate are added to the 5 ml of the plasticizer, wherein the lithium bis(fluorosulfonyl)imide and the lithium hexafluorophosphate are lithium salts, and then 2.264 g of 1,3,5-trioxane is added, wherein the 1,3,5-trioxane is a monomer, and after uniform mixing, a first mixed solution is obtained, and then 0.226 g of lithium difluorooxalate borate is added, wherein the lithium difluorooxalate borate is an initiator; wherein the mass of the initiator is 10% of the mass of the monomer; after stirring for 30 minutes, a precursor is obtained;

[0096] A soft-pack battery is assembled using graphite as the negative electrode of the lithium battery, a nickel-cobalt-manganese ternary material as the positive electrode of the lithium battery, and polypropylene as a separator; 2 mL of the precursor is injected into the battery, and after standing at room temperature for 24 hours, it is stood at a high temperature of 40°C for 2 hours to obtain a lithium battery containing a polymer solid electrolyte.

[0097] Example 16 of the preparation method of the lithium battery is as follows,

[0098] Fluorinated ethylene carbonate and methyl trifluoroethyl carbonate are mixed in a mass ratio of 1:1 to obtain a plasticizer, and 5 ml of the plasticizer is taken; 0.374 g of lithium bis(fluorosulfonyl)imide and 0.037 g of lithium hexafluorophosphate are added to the 5 ml of the plasticizer, wherein the lithium bis(fluorosulfonyl)imide and the lithium hexafluorophosphate are lithium salts, and then 2.264 g of 1,3,5-trioxane is added, wherein the 1,3,5-trioxane is a monomer, and after uniform mixing, a first mixed solution is obtained, and then 0.226 g of lithium difluorooxalate borate is added, wherein the lithium difluorooxalate borate is an initiator; wherein the mass of the initiator is 10% of the mass of the monomer; after stirring for 30 minutes, a precursor is obtained;

[0099] A soft-pack battery is assembled using graphite as the negative electrode of the lithium battery, a nickel-cobalt-manganese ternary material as the positive electrode of the lithium battery, and polypropylene as a separator; 2 mL of the precursor is injected into the battery, and after standing at room temperature for 24 hours, it is stood at a high temperature of 70°C for 2 hours to obtain a lithium battery containing a polymer solid electrolyte.

[0100] Example 17 of the preparation method of the lithium battery is as follows,

[0101] Fluorinated ethylene carbonate and methyl trifluoroethyl carbonate are mixed in a mass ratio of 1:1 to obtain a plasticizer, and 5 ml of the plasticizer is taken; 0.374 g of lithium bis(fluorosulfonyl)imide and 0.037 g of lithium hexafluorophosphate are added to the 5 ml of the plasticizer, wherein the lithium bis(fluorosulfonyl)imide and the lithium hexafluorophosphate are lithium salts, and then 2.264 g of 1,3,5-trioxane is added, wherein the 1,3,5-trioxane is a monomer, and after uniform mixing, a first mixed solution is obtained, and then 0.226 g of lithium difluorooxalate borate is added, wherein the lithium difluorooxalate borate is an initiator; wherein the mass of the initiator is 10% of the mass of the monomer; after stirring for 30 minutes, a precursor is obtained;

[0102] A soft-pack battery is assembled using graphite as the negative electrode of the lithium battery, a nickel-cobalt-manganese ternary material as the positive electrode of the lithium battery, and polypropylene as a separator; 2 mL of the precursor is injected into the battery, and after standing at room temperature for 24 hours, it is stood at a high temperature of 90°C for 2 hours to obtain a lithium battery containing a polymer solid electrolyte.

[0103] Example 18 of the preparation method of the lithium battery is as follows,

[0104] Fluorinated ethylene carbonate and methyl trifluoroethyl carbonate are mixed in a mass ratio of 1:1 to obtain a plasticizer, and 5 ml of the plasticizer is taken; 0.374 g of lithium bis(fluorosulfonyl)imide and 0.037 g of lithium hexafluorophosphate are added to the 5 ml of the plasticizer, wherein the lithium bis(fluorosulfonyl)imide and the lithium hexafluorophosphate are lithium salts, and then 2.264 g of 1,3,5-trioxane is added, wherein the 1,3,5-trioxane is a monomer, and after uniform mixing, a first mixed solution is obtained, and then 0.226 g of lithium difluorooxalate borate is added, wherein the lithium difluorooxalate borate is an initiator; wherein the mass of the initiator is 10% of the mass of the monomer; after stirring for 30 minutes, a precursor is obtained;

[0105] A soft-pack battery is assembled using graphite as the negative electrode of the lithium battery, a nickel-cobalt-manganese ternary material as the positive electrode of the lithium battery, and polypropylene as a separator; 2 mL of the precursor is injected into the battery, and after standing at room temperature for 24 hours, it is stood at a high temperature of 100°C for 2 hours to obtain a lithium battery containing a polymer solid electrolyte.

[0106] In Examples 14-17, the reaction process is the same as in Example 1, except that the temperature of the high temperature standing is changed, as shown in Table 4.

[0107] Table 4

[0108] Static temperature (℃) <![CDATA[Conductivity (mS cm -1 )]]> Lithium ion migration number Example 1 80 2.39 0.78 Embodiment 15 40 2.91 0.31 Example 16 70 2.32 0.76 Embodiment 17 90 2.21 0.73 Embodiment 18 100 2.11 0.71

[0109] The lithium ion migration number is one of the important parameters for evaluating battery performance. A higher lithium ion migration number can reduce the concentration polarization inside the battery and improve the electrochemical performance of the battery. Moreover, the higher the conductivity, the better the battery performance. The standard for high electrochemical performance of lithium batteries is set to a lithium ion migration number equal to 0.7. If the lithium ion migration number is greater than or equal to 0.7, it means that the lithium battery has high electrochemical performance. If the lithium ion migration number is greater than or equal to 0.7, it means that the lithium battery has high electrochemical performance. In Table 2, Example 1, Example 16, Example 17 and Example 18 meet the standard for high electrochemical performance of lithium batteries. Moreover, the conductivity of Example 1 is greater than the conductivity of Example 16. The conductivity of Example 1 is greater than the conductivity of Example 17, and the conductivity of Example 1 is greater than the conductivity of Example 18. The preparation method of Example 1 can make the battery performance better, and therefore, Example 1 is the best embodiment.

[0110] Therefore, combining the above embodiments and the results of conductivity and lithium ion migration number in Table 1, Table 2, Table 3, and Table 4, it can be concluded that Embodiment 1 is the best embodiment.

[0111] The present invention provides a method for preparing a lithium battery containing a polymer solid electrolyte. The polymer solid electrolyte uses a heterocyclic ring as a monomer, is mixed with an initiator, a lithium salt and a plasticizer, and then injected into a diaphragm. The heterocyclic ring monomer undergoes in-situ polymerization inside the battery according to a ring-opening polymerization mechanism. Therefore, the polymer solid electrolyte has excellent electrochemical performance, and a lithium battery with a high energy density can be obtained by matching a high-voltage positive electrode material. Therefore, the lithium battery containing a polymer solid electrolyte has good battery performance. The polymer solid electrolyte uses a lithium salt as an initiator, which is conducive to maintaining the purity of the electrolyte system and can improve the performance of the battery. The electrolyte is solid, which effectively improves the safety of the battery. The electrolyte is finally solidified between the electrodes, which significantly improves the interface contact between the electrodes and improves the cycle performance of the battery. Therefore, the lithium battery containing a polymer solid electrolyte not only has high safety, but also has good battery performance. The technical problem that the existing polymer electrolyte has an adverse effect on battery performance is effectively solved.

[0112] Moreover, the lithium battery containing polymer solid electrolyte adopts cationic ring-opening polymerization mechanism, which has the advantage of fast reaction rate. The ionic conductivity of the lithium battery containing polymer solid electrolyte can reach 2.39mS / cm, and it can maintain good electrochemical stability within 5V, and the lithium ion migration number reaches 0.78, so the lithium battery containing polymer solid electrolyte has excellent electrochemical performance. At room temperature, when the NCM811 / Gr battery is cyclically charged and discharged at a rate of 0.5C, the first cycle discharge capacity reaches 181mAh / g, and the capacity retention rate after 295 cycles reaches more than 96%. Among them, the NCM811 / Gr battery is a ternary lithium battery. The present invention adopts an in-situ polymerization method to prepare a polymer solid electrolyte, which avoids the consumption of a large amount of organic solvents in the traditional process, and can also match the existing battery production line process. It effectively saves production costs and improves the possibility of large-scale industrialization of polymer solid electrolytes.

[0113] In summary, although the present invention has been disclosed as above in terms of preferred embodiments, the above preferred embodiments are not intended to limit the present invention. A person skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be based on the scope defined in the claims.

Claims

1. A method for preparing a lithium battery containing a polymer solid electrolyte, characterized in that: It includes the following steps: S1: using lithium salt as solute and plasticizer as solvent to prepare a solution of preset concentration, wherein the preset concentration is 0.8 mol / L-2 mol / L of the lithium salt in the plasticizer; S2: uniformly mixing the monomer and the solution obtained in step S1 to obtain a mixed solution, and then adding an initiator and mixing them uniformly to obtain a precursor; wherein the mass fraction of the monomer in the mixed solution is 20-80%; the mass of the initiator is 0-20% of the mass of the monomer; S3: Assembling a lithium battery with a negative electrode of a lithium battery, a positive electrode of a lithium battery and a separator; S4: injecting the precursor obtained in step S2 into the lithium battery, and subjecting the precursor to a high-temperature standing operation within a temperature range of 40-100°C, and obtaining a lithium battery containing a polymer solid electrolyte after high-temperature standing for 1-12 hours, wherein the injection amount of the precursor is determined by the unit area of ​​the diaphragm, and the injection amount of the precursor is 20-150 μL.

2. The method for preparing a lithium battery containing a polymer solid electrolyte according to claim 1, characterized in that: In the step S2, the mass of the initiator is 5-10% of the mass of the monomer.

3. The method for preparing a lithium battery containing a polymer solid electrolyte according to claim 1, characterized in that: In the step S4, the high temperature static temperature is 70-80°C.

4. The method for preparing a lithium battery containing a polymer solid electrolyte according to claim 1, characterized in that: In step S4, the high temperature standing time is 2-4 hours.

5. The method for preparing a lithium battery containing a polymer solid electrolyte according to claim 1, characterized in that: The monomer is a cyclic ether, a cyclic lactone or a cyclic carbonate. The cyclic ether is composed of a mixture of one or more of 1,3,5-trioxane, 1,3-dioxolane, ethylene oxide, epichlorohydrin, 1,2-propylene oxide, 1,3-propylene oxide, 1,2-butylene oxide and tetrahydrofuran; the cyclic lactone is composed of a mixture of one or more of ε-caprolactone, γ-butyrolactone, δ-valerolactone and lactide; and the cyclic carbonate is composed of a mixture of one or more of vinyl ethylene carbonate and trimethylene carbonate.

6. The method for preparing a lithium battery containing a polymer solid electrolyte according to claim 1, characterized in that: The initiator is composed of one or more mixtures of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorooxalatoborate, stannous isooctanoate, aluminum trifluoromethanesulfonate, boron trifluoride ethyl ether, and tris(pentafluorophenyl)borane.

7. The method for preparing a lithium battery containing a polymer solid electrolyte according to claim 1, characterized in that: The lithium salt is composed of any one or more mixtures of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium difluorooxalatoborate, lithium perchlorate, lithium bisoxalatoborate, lithium trichloromethylsulfonate, lithium bistrifluoromethylsulfonyl imide, and lithium bisfluorosulfonyl imide.

8. The method for preparing a lithium battery containing a polymer solid electrolyte according to claim 1, characterized in that: The plasticizer is composed of one or more mixtures of ethylene carbonate, propylene carbonate, vinylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, fluoroethylene carbonate, 2,2,2-trifluoro-N,N-dimethylacetamide, methyl trifluoroethyl carbonate, and triethyl phosphate.

9. The method for preparing a lithium battery containing a polymer solid electrolyte according to claim 1, characterized in that: The negative electrode of the lithium battery is any one of graphite, soft carbon, hard carbon, silicon, and lithium metal; the positive electrode of the lithium battery is any one of lithium iron phosphate, nickel-cobalt-manganese ternary material, nickel-cobalt-aluminum ternary material, lithium cobalt oxide, and lithium manganese oxide; the diaphragm is any one of polyethylene diaphragm, polypropylene diaphragm, polyimide diaphragm, cellulose diaphragm, glass fiber diaphragm, polyethylene terephthalate diaphragm, and non-woven fabric diaphragm.

10. A method for manufacturing a lithium battery, characterized in that: These include, Fluorinated ethylene carbonate and methyl trifluoroethyl carbonate are mixed in a mass ratio of 1:1 to obtain a plasticizer, and 5 ml of the plasticizer is taken; 0.374 g of lithium bis(fluorosulfonyl)imide and 0.037 g of lithium hexafluorophosphate are added to the 5 ml of the plasticizer, wherein the lithium bis(fluorosulfonyl)imide and the lithium hexafluorophosphate are lithium salts, and then 2.264 g of 1,3,5-trioxane is added, wherein the 1,3,5-trioxane is a monomer, and after uniform mixing, a first mixed solution is obtained, and then 0.226 g of lithium difluorooxalate borate is added, wherein the lithium difluorooxalate borate is an initiator; after stirring for 30 minutes, a precursor is obtained; A soft-pack battery is assembled using graphite as the negative electrode of the lithium battery, a nickel-cobalt-manganese ternary material as the positive electrode of the lithium battery, and polypropylene as a separator; 2 mL of the precursor is injected into the battery, and after standing at room temperature for 24 hours, it is stood at a high temperature of 80°C for 2 hours to obtain a lithium battery containing a polymer solid electrolyte.